До питання локалізації літописного Моклекова - Миська, Р. (Інститут українознавства ім. І. Крип'якевича НАН України, 2009)
Issue of localization of annalistic city of Moklekiv is analuzed at this article. For example, hypnotize presented by L. Mahnovets’ about correlation of this settlement with three hill-forts, situated near village Bile (Chortkiv District, Ternopil region) is verified on the base of excavations, carried out by the author.Archaeological researches shows that largest hill-fort (Bila I) is dated back to the end of IX–X century. It can be interpreted as hill-fort (prince’s fortress). Two other hill-forts are situated on left bank of Seret River and dated to XII–XIII centuries. They can be correlated with annalistic Moklekiv. But for decision of this question new stationary archaeological excavations are needed.